Dehydroabietic Acid Microencapsulation Potential as Biofilm-Mediated Infections Treatment - Iris Neto; Eva María Domínguez-Martín; Epole Ntungwe; Catarina P. Reis; Milica Pesic; Célia Faustino; Patrícia Rijo (MDPI AG, 2021)
The antimicrobial activity of dehydroabietic acid (DHA) for its use as an antibiofilm agent was tested in this work. DHA was assayed against a collection of Gram-positive, Gram-negative sensitive and resistant bacteria and yeasts through the minimum inhibitory concentration (MIC), MIC with Bioburden challenge, minimum bactericidal concentration (MBC), minimum biofilm inhibitory concentration (MBIC), MBIC with Bioburden challenge and growth curve studies. Toxicological studies (Artemia salina, sulforhodamine B (SRB) assay) were done to assess if the compound had antimicrobial and not cytotoxic properties. Furthermore, microencapsulation and stability studies were carried out to evaluate the chemical behavior and stability of DHA. On MIC results, Gram-positive bacteria Staphylococcus aureus ATCC 1228 and Mycobacterium smegmatis ATCC 607 presented a high efficiency (7.81 µg/mL), while on Gram-negative bacteria the highest MIC value of 125 µg/mL was obtained by all Klebsiella pneumoniae strains and Escherichia coli isolate strain HSM 303. Bioburden challenge showed that MIC, MBIC and percentage biofilm inhibition (BI) values suffered alterations, therefore, having higher concentrations. MBIC values demonstrated that DHA has a higher efficiency against S. aureus ATCC 43866 with a percentage of BI of 75.13 ± 0.82% at 0.49 µg/mL. Growth curve kinetic profiles of DHA against S. aureus ATCC 25923 were observed to be bacteriostatic. DHA-alginate beads had a average size of 2.37 ± 0.20 and 2.31 ± 0.17 × 103 µm2 with an encapsulation efficiency (EE%) around 99.49 ± 0.05%, a protection percentage (PP%) of 60.00 ± 0.05% in the gastric environment and a protection efficiency (PE%) around 88.12 ± 0.05% against UV light. In toxicological studies DHA has shown IC50 of 19.59 ± 7.40 µg/mL and a LC50 of 21.71 ± 2.18%. The obtained results indicate that DHA is a promising antimicrobial candidate against a wide range of bacteria and biofilm formation that must be further explored.